2007
DOI: 10.1007/s11199-007-9351-9
|View full text |Cite
|
Sign up to set email alerts
|

Doing and Undoing Gender in Sport Governance

Abstract: Processes of sense making enable individuals to explain or give meaning to their experiences including those pertaining to gender. Meanings shape both individual behaviors and expectations for the behavior of others. The purpose of this exploratory study was to examine how board members of national sport associations in the Netherlands made sense of gendered arrangements. We used a sense making approach that acknowledges the significance of context (gender ratio) and constructions of meaning in shaping organiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
1
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 84 publications
(63 citation statements)
references
References 23 publications
0
58
1
4
Order By: Relevance
“…The articles in the Special Issue have adopted varied methodological approaches, including indepth semi-structured qualitative interviews (Bruening and Dixon 2008;Claringbould and Knoppers 2008;FieldingLloyd and Mean 2008;Hoeber 2008;Ross and Shinew 2008), critical discourse analyses (Knoppers and Anthonissen 2008), participant observations (Anderson 2008), survey research (Avery et al 2008), and laboratory experiments (Angelini 2008;Parker and Fink 2008). The diversity of approaches to the study of sex and gender in sport organizations provides an encompassing perspective-one that allows for a more complete understanding of gender in the workplace.…”
Section: Varied Methodologiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The articles in the Special Issue have adopted varied methodological approaches, including indepth semi-structured qualitative interviews (Bruening and Dixon 2008;Claringbould and Knoppers 2008;FieldingLloyd and Mean 2008;Hoeber 2008;Ross and Shinew 2008), critical discourse analyses (Knoppers and Anthonissen 2008), participant observations (Anderson 2008), survey research (Avery et al 2008), and laboratory experiments (Angelini 2008;Parker and Fink 2008). The diversity of approaches to the study of sex and gender in sport organizations provides an encompassing perspective-one that allows for a more complete understanding of gender in the workplace.…”
Section: Varied Methodologiesmentioning
confidence: 99%
“…Various authors in the Special Issue have specifically addressed this issue. For instance, Claringbould and Knoppers (2008) pointed to the need to examine the interconnectedness between organizational structures and behaviors of organizational members. Cunningham (2008), in his framework for creating and sustaining gender equality in sport organizations, argued that institutional forces (macro), organizational policies (meso), and individual commitment to gender equality and the behavioral manifestations thereof (micro) all contribute to the change process.…”
Section: Multilevel Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…This type of behavior is typical of "token" women in male-dominated professions (Kanter, 1977;Richie et aI., 1997;Whitmarsh et aI., 2007), including sport management (Claringbould & Knoppers, 2008;Grappendorf & Lough, 2006;Grappendorf et aI., 2004) Skill acquisition and development are important because women in this study perceived them to be essential for career advancement. The idea of advancement is complex.…”
Section: As Julian Explainedmentioning
confidence: 73%
“…Male and female administrators should work to create more seats the proverbial "table." Studies have shown organizations with a more diverse (i.e., gender and race) staff are more productive (Catalyst, 2011;Claringbould & Knoppers, 2008;Elstad & Ladegard, 2010).…”
Section: Implications For Sport Managersmentioning
confidence: 99%